2000
DOI: 10.1086/302755
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 6p Influences on Different Dyslexia-Related Cognitive Processes: Further Confirmation

Abstract: In this study, which is a continuation and an extension of an earlier study, we enrolled two new families (N=31) and recruited more individuals from the previously ascertained families (N=56). The eight multiplex families (N=171) presented in this study were ascertained from a sample of adult probands whose childhood reading history is well documented through archival information. Six phenotypes were constructed to span a range of dyslexia-related cognitive processes. These phenotypes were (1) phonemic awarene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
129
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(139 citation statements)
references
References 13 publications
6
129
0
4
Order By: Relevance
“…This independence may ultimately be supported at a molecular genetic level if specific genes are found to have stronger effects on deficits in specific component reading and language skills. Recent linkage studies suggest that such process-specific genes may exist, although given the large genetic correlations among reading and language skills obtained in this study, genes with large effects are most likely common to most of these reading skills (Fisher et al, 1999;Grigorenko et al, 1997;Grigorenko, Wood, Meyer, & Pauls, 2000).…”
Section: Implications Of the Results For Theory Etiology And Remedimentioning
confidence: 71%
“…This independence may ultimately be supported at a molecular genetic level if specific genes are found to have stronger effects on deficits in specific component reading and language skills. Recent linkage studies suggest that such process-specific genes may exist, although given the large genetic correlations among reading and language skills obtained in this study, genes with large effects are most likely common to most of these reading skills (Fisher et al, 1999;Grigorenko et al, 1997;Grigorenko, Wood, Meyer, & Pauls, 2000).…”
Section: Implications Of the Results For Theory Etiology And Remedimentioning
confidence: 71%
“…[1][2][3][4][5][6][7][8] Linkage studies have identified several genomic regions that may harbor susceptibility quantitative trait loci (QTL) for DD, and the most consistently replicated of these is DYX2, which lies on chromosome 6p22.2. 1,[9][10][11][12][13][14][15][16] A number of association studies have now been performed attempting to identify the DYX2 susceptibility locus. In independent samples from the UK and the US, we previously found evidence that variation in the KIAA0319 gene confers risk of dyslexia.…”
Section: Introductionmentioning
confidence: 99%
“…While reports of linkage of RWR phenotypes to chromosomes 1p (Grigorenko et al, 2001) and 2p (Loo et al, 2004) have not yet been replicated, several other regions have shown reproducible evidence for linkage in more than one sample. Evidence for linkage for RWR has been reported for chromosomes 6p (DYX2, OMIM 600202, http://www.ncbi.nlm.nih.gov/omim) (Cardon et al, 1994;Cardon et al, 1995;Fisher et al, 1999;Grigorenko et al, 2003;Grigorenko et al, 1997;Grigorenko et al, 2000;Kaplan et al, 2002), 15q (locus DYX1, OMIM 127700) (Chapman et al, 2004;Grigorenko et al, 1997;Marino et al, 2004;Nopola-Hemmi et al, 2000;Smith et al, 1983), and 18p (DYX6, OMIM 606616) Marlow et al, 2003).…”
Section: Introductionmentioning
confidence: 99%